A metric-based evaluation model for applications on mobile phones - Hussain, Azham; Hashim, Nor Laily; Nordin, Nazib; Mohamad Tahir, Hatim (Universiti Utara Malaysia Press, 2013)
A number of methods and measures have been used by researchers in software evaluation. Usability metrics is one of the approaches that has been used as a guideline to evaluate the quality of the system in many mobile applications.However, the metrics used for evaluation method keep changing due to new inventions of mobile phones.Thus, there is a need to create a dynamic model for evaluation that can grow together with new inventions and technology.In this paper, a dynamic usability metrics model for evaluation of mobile applications was designed.The model comprises usability goals, questions and metrics for evaluation of applications on mobile phones. To ensure that the model is reliable and effective, a usability study was conducted on two applications installed in different mobile phones.This model proves to be applicable for evaluation of mobile phone applications whereby its questions and metrics can be dynamically changed accordingly to comply with the requirements of the evaluators.